Conversion of Anergic T Cells Into Foxp3- IL-10+ Regulatory T Cells by a Second Antigen Stimulus In Vivo - Thomann, Anna Sophie; Schneider, Theresa; Cyran, Laura; Eckert, Ina Nathalie; Kerstan, Andreas; Lutz, Manfred B. (Frontiers in Immunology, 2021)
T cell anergy is a common mechanism of T cell tolerance. However, although anergic T cells are retained for longer time periods in their hosts, they remain functionally passive. Here, we describe the induction of anergic CD4+ T cells in vivo by intravenous application of high doses of antigen and their subsequent conversion into suppressive Foxp3- IL-10+ Tr1 cells but not Foxp3+ Tregs. We describe the kinetics of up-regulation of several memory-, anergy- and suppression-related markers such as CD44, CD73, FR4, CD25, CD28, PD-1, Egr-2, Foxp3 and CTLA-4 in this process. The conversion into suppressive Tr1 cells correlates with the transient intracellular CTLA-4 expression and required the restimulation of anergic cells in a short-term time window. Restimulation after longer time periods, when CTLA-4 is down-regulated again retains the anergic state but does not lead to the induction of suppressor function. Our data require further functional investigations but at this stage may suggest a role for anergic T cells as a circulating pool of passive cells that may be re-activated into Tr1 cells upon short-term restimulation with high and systemic doses of antigen. It is tentative to speculate that such a scenario may represent cases of allergen responses in non-allergic individuals.